Penguatan Ikatan Pernikahan melalui Program “Pernikahan yang Dilahirkan Kembali” di GPPS Agape Bandung - Darmawan Darmawan; Fransisca Putri Cyndivania; Veronicha Nussa; Andronius Wedo; Hotmantri Simbolon (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
A faith-based marriage strengthening program is essential for building family resilience in urban congregations facing high divorce rates and declining marital quality. This community service activity aimed to revitalize the marital bonds of 22 couples in the Pria Sejati Bandung community and GPPS Agape Bandung congregation through the